Empowerment of Plastic Webbing Outlets through Visual Promotion Training Using Augmented Reality (AR) Websites and Social Media - Sefanda, Sakti Kalisa; Nuraini, Lailatul; Triwulandari, Ike; Hariyanto, Moh Rifki; Rohim, Khisan Afif Ainur; Unisation, Disa Amartha (Faculty of Mathematics and Natural Sciences, University of Jember. Jl. Kalimantan No.37, Krajan Timur, Jemberlor, Kec. Sumbersari, Jember Regency, East Java 68121, 2025)
Gumuk-Kembar Plastic Woven Outlet is an MSME engaged in handicraft entrepreneurship from plastic rope material. This wicker outlet is able to open new business opportunities for housewives around partners. The Plastic Woven Outlet MSMEs have problems in terms of marketing carried out, with this increasingly advanced era, technology is also running quickly. The purpose of this community service activity is to foster community creativity in managing MSMEs with a more modern visual promotion strategy in the form of 3-dimensional animation in order to increase consumer interest. Service activities in the form of socialization using lecture or presentation methods and the application of AR-based website media, and continued by providing user response questionnaires. Data collection techniques use observation, interviews and questionnaires. Data analysis techniques use SPSS descriptive statistical methods. The result of this activity is to increase the creativity of craftsmen in utilizing technology in the business world and being able to manage MSMEs appropriately and efficiently and user response to the use of augmented reality website-based visual promotions was 82.79% in the very good category